2019
DOI: 10.3389/fvets.2019.00461
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Pathogen Screening of Captive Reindeer (Rangifer tarandus) in Germany Based on Serological and Molecular Assays

Abstract: Captive reindeer in German zoos and wildlife parks live outside their natural geographic range and are exposed to a variety of viral, bacterial and protozoan pathogens, some host-specific and some which they are not exposed to in their native habitat. Reindeer blood samples and ticks collected in 2013 from 123 reindeer at 16 different zoological facilities were available from a previous study. The aims of this study were to assess the serological status of these animals with regards to various microorganisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 69 publications
(79 reference statements)
0
29
0
Order By: Relevance
“…Previous studies used a competitive ELISA with an antigen based on a conserved epitope among all known members of the malignant catarrhal fever virus group. These studies showed 5.9% seropositivity in captive Eurasian reindeer from Germany (n = 119) [39], 4% in wild Eurasian reindeer from Norway (n = 250) and porcupine caribou from Alaska (n = 232) [40], and 3.5% (n = 3339) in apparently healthy, semi-domesticated Eurasian reindeer from Finnmark County, northern Norway [28]. Such findings contrasted with the prevalence we obtained in this study by PCR (28.2% and 48.6% in semi-domesticated and wild reindeer, respectively).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies used a competitive ELISA with an antigen based on a conserved epitope among all known members of the malignant catarrhal fever virus group. These studies showed 5.9% seropositivity in captive Eurasian reindeer from Germany (n = 119) [39], 4% in wild Eurasian reindeer from Norway (n = 250) and porcupine caribou from Alaska (n = 232) [40], and 3.5% (n = 3339) in apparently healthy, semi-domesticated Eurasian reindeer from Finnmark County, northern Norway [28]. Such findings contrasted with the prevalence we obtained in this study by PCR (28.2% and 48.6% in semi-domesticated and wild reindeer, respectively).…”
Section: Discussionmentioning
confidence: 94%
“…Hence, formal molecular identification of Babesia sp. in wild ruminants is routinely performed (12).…”
Section: Discussionmentioning
confidence: 99%
“…Disease due to Anaplasma phagocytophilum infection has not been fully described in reindeer, even if the infection seems moderately prevalent (12). The infection in domestic and wild ruminants results in a seldom fatal disease unless complicated by other infections (2,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations